2019
DOI: 10.5812/ircmj.96672
|View full text |Cite
|
Sign up to set email alerts
|

Pramipexole Versus Selegiline in Patients with Parkinson’s Disease: An Effectiveness and Safety (EAS) Analysis

Abstract: Background: Levodopa treatment is the gold standard in Parkinson's disease but has the risk of dyskinesias. Selegiline delays the introduction of levodopa and pramipexole is used as a symptomatic treatment in Parkinson's disease. Objectives: This study aimed to compare the effectiveness of pramipexole with selegiline in Parkinson's disease patients. Methods: Data regarding motor and cognitive impairments and plasma phospholipids of 500 Chinese patients with confirmed Parkinson's disease from medical records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…A total of 38 studies (6,338 patients) were included in the systematic review, including 27 RCTs and 11 observational studies ( Table 1 ). Twenty-three studies (Presthus et al, 1987 ; Hietanen, 1991 ; Nappi et al, 1991 ; Allain et al, 1993 ; Lees, 1993 ; Myllylä et al, 1993 ; Shoulson, 1993 , 1996 ; Mally et al, 1995 ; Olanow et al, 1995 ; Larsen and Boas, 1997 ; Pålhagen et al, 1998 , 2006 ; Larsen et al, 1999 ; Lyytinen et al, 2000 ; Shoulson et al, 2002 ; Weng et al, 2002 ; Su et al, 2004 ; Zhao et al, 2004 , 2005 ; Ye et al, 2014 ; Mizuno et al, 2017 ; Tao et al, 2019 ) reported the outcome which is also reported in at least one other study, and were included in the meta-analysis, and the results of other studies were described in term of outcomes. Selegiline treatment duration ranged from 2 weeks to 7 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 38 studies (6,338 patients) were included in the systematic review, including 27 RCTs and 11 observational studies ( Table 1 ). Twenty-three studies (Presthus et al, 1987 ; Hietanen, 1991 ; Nappi et al, 1991 ; Allain et al, 1993 ; Lees, 1993 ; Myllylä et al, 1993 ; Shoulson, 1993 , 1996 ; Mally et al, 1995 ; Olanow et al, 1995 ; Larsen and Boas, 1997 ; Pålhagen et al, 1998 , 2006 ; Larsen et al, 1999 ; Lyytinen et al, 2000 ; Shoulson et al, 2002 ; Weng et al, 2002 ; Su et al, 2004 ; Zhao et al, 2004 , 2005 ; Ye et al, 2014 ; Mizuno et al, 2017 ; Tao et al, 2019 ) reported the outcome which is also reported in at least one other study, and were included in the meta-analysis, and the results of other studies were described in term of outcomes. Selegiline treatment duration ranged from 2 weeks to 7 years.…”
Section: Resultsmentioning
confidence: 99%
“…UPDRS II score was significantly improved among patients treated with selegiline compared with patients treated with levodopa, bromocriptine, and lisuride (Caraceni et al, 1992 ). One observational study showed the improvement in UPDRS III was higher for pramipexole than selegiline (Tao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%